«Tra quanto resta di macerie». Le rovine di guerra nell’Italia del Novecento - Gennaro, Tommaso (L'ospite ingrato, 2023)
This article analyzes the meaning of war debris in twentieth century Italian poetry. After a quick survey aimed at assessing its frequency and incidence, attention will focus on some authors who have poetically elaborated the presence of war debris as traces of a past-present that does not cease to last.